1990
DOI: 10.1128/aac.34.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose oral cefixime versus amoxicillin plus probenecid for the treatment of uncomplicated gonorrhea in men

Abstract: In this randomized study, a single 800-mg oral dose of cefixime cured 96 of 97 men with uncomplicated gonococcal urethritis, compared with 44 cures of 46 men who received standard therapy with amoxicillin (3 g) plus probenecid (1 g). Both regimens were ineffective against coexistent infection with Chiamydia trachomatis and Ureaplasma urealyticum. Cefixime was well tolerated, and all side effects were mild and self-limited.Cefixime is a novel oral cephalosporin with ,-lactamase stability and in vitro activity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…17 In Japan, where the efficacy of oral regimens with fluoroquinolone and cephalosporin is failing, 11,18 the emergence of resistance to ceftriaxone and specinomycin in clinical strains of N. gonorrhoeae, which would be disastrous for the treatment of gonococcal infections, must be prevented. At the same time, because oral regimens are clinically more convenient for the treatment of gonococcal urethritis, new oral regimens, including a single-dose regimen with an increased dose of cefixime; for example, a single dose of 800 mg cefixime or more, 9,[19][20][21][22] must be developed.…”
Section: Discussionmentioning
confidence: 99%
“…17 In Japan, where the efficacy of oral regimens with fluoroquinolone and cephalosporin is failing, 11,18 the emergence of resistance to ceftriaxone and specinomycin in clinical strains of N. gonorrhoeae, which would be disastrous for the treatment of gonococcal infections, must be prevented. At the same time, because oral regimens are clinically more convenient for the treatment of gonococcal urethritis, new oral regimens, including a single-dose regimen with an increased dose of cefixime; for example, a single dose of 800 mg cefixime or more, 9,[19][20][21][22] must be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen of these studies reported adverse reactions in 569 patients and the safety of 11 drugs was assessed [27][28][29][30][31][32][33][34][36][37][38][39][40][41][44][45][46]49,50]. Similarly, 19 studies focused on oral monotherapy [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. These studies of oral drugs involved 3782 patients, and compared the efficacy of 11 antibiotics.…”
Section: Literature Search Process and Study Characteristicsmentioning
confidence: 99%
“…Cefixime eradicated also 75% (6/8) [25] to 93% (14/15) [19] of pharyngeal gonococcal infections. The number of documented-treated rectal infections is quite low, but so far, 100% eradication of Neisseria gonorrhoea from the rectum was achieved [19.25].…”
Section: Discussionmentioning
confidence: 92%
“…Treatment of uncomplicated gonorrhoea with a single oral dose of 800 mg cefixime achieved cure rates of 98% (86/88) [19] to 99% (96/97) [25]. A single oral dose of 400 mg cefixime resulted in cure rates ranging from 96%; (89/93) [19] to 98% (118/121) [16], and even reducing the dose to 200 mg cefixime seemed to be effective, with a cure rate of 95%' (93/98) [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation